Pendekatan Saintifik dalam Peningkatan Keaktifan Siswa pada Pembelajaran Agama Islam di SMANegeri 1 Peukan Bada Kabupaten Aceh Besar - Eka Mayasari; Arisnaini Arisnaini (2021)
The scientific approach includes five steps, namely observing, asking, gathering information, processing information, and communicating. The implementation of the scientific approach in PAI lessons at SMA Negeri 1 Peukan Bada is taken in several steps, there are inhibiting factors that need to be continuously improved in order to increase student learning activity. The focus of this research is related to the implementation, steps and factors supporting and inhibiting the scientific approach to increase student activity in PAI learning. This research is in the form of verbal qualitative with a descriptive approach. Collecting data through observation, interviews and documentation. The implementation of PAI learning by applying a scientific approach model in learning that has been applied to students of SMA Negeri 1 Peukan Bada by increasing discipline, order and maximizing study hours, learning with scientific steps, increasing student activity by way of students being involved in the teaching and learning process. The ability of PAI teachers in applying the scientific model in learning and being able to manage the class well, so that students become more active in learning becomes a fun thing. The scientific approach to increase student learning activity is done by stimulating concepts, asking questions about concepts, facilitating information gathering, guiding to build arguments, and guiding to conclude the concepts being taught. Supporting factors can be influenced in terms of the ability of teachers, improved school facilities, teacher training, availability of supporting books and laboratories. The inhibiting factor is in terms of the currently inadequate facilities and there are still some teachers who are not fully capable of carrying out a scientific approach in learning.